Hubungan Pemanfaatan Aplikasi Senior Smart dengan Tingkat Pengetahuan Peserta Didik di Sekolah Lansia Tangguh Kota Pasuruan - Sephia Arini, Nur; Kurniasih, Dwi Endah (IAI Nasional Laa Roiba Bogor, 2024)
Pasuruan City will enter an aging population. One of the programs carried out is senior smart in increasing knowledge. Activities are accelerated using the senior smart application. Objective: Knowing the relationship between the use of the Senior Smart application and the level of knowledge of students of Pasuruan City's resilient elderly school. Research Method: This type of study used a cross-sectional research design with a sample of 150 elderly school students in Pasuruan City. The implementation of activities from August to September 2023, data was collected by questionnaire and analyzed by spearmen test. Results: 100% utilization of senior smart applications, knowledge level in high category as much as 97.3%. The spearmen test results show p-value = 0.045 and correlation coefficient value of 0.164. Conclusion: There is a relationship between the use of senior smart applications and the level of knowledge of resilient elderly school students in Pasuruan City